2023
DOI: 10.1001/jamanetworkopen.2023.9990
|View full text |Cite
|
Sign up to set email alerts
|

Association of Integrating Mental Health Into Pediatric Primary Care at Federally Qualified Health Centers With Utilization and Follow-up Care

Abstract: ImportanceMore than 1 in 5 children in low-income families report a mental health (MH) problem, yet most face barriers accessing MH services. Integrating MH services into primary care at pediatric practices such as federally qualified health centers (FQHCs) may address these barriers.ObjectiveTo examine the association of a comprehensive MH integration model with health care utilization, psychotropic medication use, and MH follow-up care among Medicaid-enrolled children at FQHCs.Design, Setting, and Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The AAP stresses that screening with validated instruments supplements developmental surveillance and should be administered anytime a concern arises from the clinician, parents, or early childhood professionals (AAP Developmental Surveillance and Screening Initiative, 2022). Valid detection is especially crucial in early childhood where developmental discernment is so challenging (Kim et al, 2023). A universal approach is of particular importance for advancing an antiracism stance that mitigates implicit biases, which are attenuated when all children routinely receive the same assessment (Allen et al, 2010; Sheldrick et al, 2022).…”
Section: Decisional Uncertainty Impedes the Potential Of Pediatric Ca...mentioning
confidence: 99%
“…The AAP stresses that screening with validated instruments supplements developmental surveillance and should be administered anytime a concern arises from the clinician, parents, or early childhood professionals (AAP Developmental Surveillance and Screening Initiative, 2022). Valid detection is especially crucial in early childhood where developmental discernment is so challenging (Kim et al, 2023). A universal approach is of particular importance for advancing an antiracism stance that mitigates implicit biases, which are attenuated when all children routinely receive the same assessment (Allen et al, 2010; Sheldrick et al, 2022).…”
Section: Decisional Uncertainty Impedes the Potential Of Pediatric Ca...mentioning
confidence: 99%
“…22,23 Prior publications describe implementation of the key core components of the TEAM UP model. [15][16][17]24 All sites implemented enhanced screening in multiple languages for all age groups. Screening rates averaged 80%, consistently surpassing state benchmarks.…”
Section: Study Settingmentioning
confidence: 99%
“… 15 Comparisons with non–TEAM UP FQHCs using claims data demonstrate that after 1.5 years of implementation, TEAM UP was associated with increases in primary care visit rates, particularly among children with mental health disorders, increases in mental health service use, decreases in psychotropic medication use, with no changes in the total cost of care, inpatient admission, or follow-up care. 16 , 17 Like other pragmatic studies of integrated care models, 18 these analyses rely on data from EMR and insurance claims databases, both of which can be analyzed without direct data collection from patients. However, a limitation of these data sources is that they do not capture important domains of patients' experience.…”
mentioning
confidence: 99%
“…14 This care could have been improved through care coordination and mental health integration. 15,16 Emergency department (ED) visits remain a persistent problem and often serve as an indicator of integrated primary care through care coordination because lacking access to a PCMH results in higher ED visits. 1,17 Lo et al 18 found that pediatric ED visits have risen between 2007 and 2016 for various reasons (MHDs 60%, deliberate self-harm 329%, substance abuse 159%, and living in rural and semirural communities 41%), whereas the volume of overall pediatric ED visits remained unchanged.…”
Section: Introductionmentioning
confidence: 99%